Fibrolipomatous hamartoma of the digital branches of the median nerve - Hossain, MM; Momen, MM; Haque, AKM F (Pulse, 2011)
Fibrolipomatous Hamartoma is an idiopathic disorder which may be related to hypertrophy of mature fat cells and fibroblasts in the epineurium. It is a rare condition most commonly affects the median nerve. Presentation is usually before 30 years of age. Some of them are presented with signs and symptoms of nerve entrapment and some are associated with macrodactyly (macrodystrophia lipomatosa) with gross cosmetic abnormality. MRI can be an important preoperative diagnostic tool. Biopsy and histopathology report can confirm the pathology. This report describes a case of Fibrolipomatous Hamartoma of the digital branches of left index and middle fingers of median nerve associated with macrodactyly. A 25-year old male patient having this problem came to Apollo Hospitals Dhaka with abnormally large left index and middle finger. Debulking by excision of the lipomatous tissue along the digital branches of median nerve was performed. Three weeks postoperatively, the patient had no major complaints and the mass decreased in size without any motor or functional losses. Sensory function also found near normal with a small area of numbness at the tip of the left index finger. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6967 Pulse Vol.4 January 2010 p.40-42